Catalyst-free [3+2] cycloaddition of azodicarbonyls and o-hydroxyaryl azomethine ylides on water. (22nd October 2021) - Wu, Zi-Qiao; Zhang, Mei-Rong; Zhou Han-Chen, Xiao-Yu; Yang, Jia-Le; Zhang, Yu-Heng; Li, Wen-Hai
Abstract: An environment-friendly methodology for the synthesis of 1, 2, 4-triazoline derivatives on water is described. This method provides an environmental and useful strategy for catalyst-free synthesis of 1, 2, 4-triazolines derivatives. The gram scale reaction and one-pot reaction are also performed to ensure the scalability and high efficiency of the reaction. Graphical abstract: Image 1